CUSTOMER RELATIONSHIP MANAGEMENT DALAM MEMPERKUAT BRAND AWARENESS COFFEE SHOP STRING BANDUNG - Hasim; Devi Fitria Sriheriyanty1 (UKRI, 2026)
This study examines the Customer Relationship Management (CRM) strategy in strengthening brand awareness at Coffee shop String Bandung, a vintage-themed coffee business targeting the youth market (Gen Z) amid the intense competition in the F&B industry. Coffee shop String has been established for only three years and has not yet gained widespread public recognition. The main issue faced is the lack of brand awareness among the public. This study aims to explore how CRM strategies implemented by Coffee shop String Bandung contribute to enhancing brand awareness among its consumers. This research adopts a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. The findings reveal that Coffee shop String applies the CRM stages of acquire (attracting new customers through social media and visual branding), enhance (strengthening relationships with customers by creating creative digital content), and retain (retaining customers through community-based approaches and loyalty programs). These strategies are executed through personalized service, digital engagement on social media, and loyalty initiatives. The CRM approach significantly contributes to the development of brand awareness, as evidenced by increased customer interaction, visual brand recognition, and spontaneous brand recall and top-of-mind awareness. This study is expected to provide theoretical contributions to the development of marketing communication studies and serve as a practical reference for F&B business practitioners seeking to strengthen their brand positioning. Keywords: Communication, Relationship Management, Brand Awareness.